LOCALIZAÇÃO E RESTAURAÇÃO AMBIENTAL DAS NASCENTES DOS PRINCIPAIS AFLUENTES DO RIO SANTO CRISTO - Oliveira, Débora M. d.; Chassot, Tatiane; Reis, Denize I.; Battisti, Iara D. E.; Garcia, Juliano R. A.; Diel, Maria I. (Salão do Conhecimento, 2013)
Resumo